One Day Service Model Towards Community Satisfaction in Peaceful Villages Watang Sidenreng District - Siti Hardyta Triana; A.Astina; Ahmad Mannu (MultiTech Publisher, 2024)
This research is quantitative research with a descriptive approach. The population in this study were all people who received services at the Peace Village Office during the last two months. The sampling technique in this research is by using saturated samples. So the population in this study is the same as the sample size, namely 77 people. Data analysis uses multiple regression analysis to hypothesize the one day service model on community satisfaction. The results of multiple linear analysis show that the one day service model has a positive effect on the level of community satisfaction. The results of the research show that the implementation of the one day service model, in this case the one day service at the Peace Village Office, has gone well. Likewise with the level of community satisfaction with public services, where the people of Peace Village feel satisfied with the public services they receive.